Serum and exhaled breath condensate leptin levels in asthmatic and obesity children: a pilot study. (27th September 2017) - Bodini, A; Tenero, L; Sandri, M; Maffeis, C; Piazza, M; Zanoni, L; Peroni, D; Boner, A; Piacentini, G
Abstract: Background : Recent studies have highlighted the possible involvement of leptin in inflammation. The leptin receptor is also expressed by alveolar macrophages, T lymphocytes and bronchial epitelial cells, suggesting a possible role in the cascade of airway inflammation. Objectives : The aim of the study was to evaluate the levels of leptin in exhaled breath condensate (EBC) from asthmatic, normal- and overweight children, in relationship with airway inflammation. Methods : 15 asthmatic non-obese children, 15 healthy non-asthmatic non-obese children, 11 obese children with asthma (OA) and 20 obese children without asthma (ONA) were enrolled. Body impedance of body weight, EBC collection, FeNO, spirometry and a blood sampling for serum leptin were assessed. Results : Leptin EBC levels were significantly higher (3.9 ng ml −1 ± 1.3) in overweight children than those obese with asthma (3.6 ng ml −1 ± 1.6; p = 0.97), non-owerweight asthmatics (2.2 ng ml −1 ± 1.2; p < 0.0001) and in healthy children (0.9 ng ml −1 ± 0.6; p < 0.001). Leptin EBC levels in asthmatic children were significantly higher than in healthy children ( p = 0.05). Leptin serum levels were significantly higher in the overweight children compared with the asthmatics (12.7 ng ml −1 ± 13.2; p < 0.001) and the healthy group (11.1 ng ml −1 ± 11.2; p < 0.001). We observed a significant correlation between EBC-leptin levels and the serum-leptin levels ( p = 0.001). No correlations were found between EBC-leptin levels, FeNO and lung function. Conclusions : This study shows that leptin is measurable in EBC in children and that EBC-leptin levels are significantly higher in the obese subjects and in asthmatic ones compared with healthy subjects. Leptin may therefore represent a non-invasive marker of non-specific airway inflammation in children.